The health of the people : the African regional report (WHO BrazzavilleCG, 2006)
Provides an overview of the public health situation across the 46 member states of the African Region of the World Health Organisation. Charts progress made to date in fighting disease and promoting health in the African Region. Reviews the success stories and looks at areas where more efforts are needed to improve people's health.
Keywords: PUBLIC HEALTH